Comparative of Environmental Law Enforcement Based on Legal Pluralism in Indonesia and Hungary: Efforts to Protect Indigenous Communities in Achieving Sustainable Environmental Governance - Bhyasa, Putu Paramaditya Bhaskara; Kurniawan, I Gede Agus; Nikolet, Talabos Dávidné Lukács (SASI, 2026)
Introduction: Environmental law enforcement is a comprehensive effort that involves all aspects, including indigenous communities, by accommodating the perspective of legal pluralism. Purposes of the Research: This research focuses on analyzing environmental law enforcement based on the concept of legal pluralism and efforts to protect indigenous communities in Indonesia and Hungary as an effort to achieve sustainable environmental governance. Methods of the Research: This research is a normative legal study with a conceptual, comparative, and legislative approach. Results of the Research: Environmental law enforcement based on legal pluralism must be grounded in the concept of environmental sustainability, which is based on several principles, namely the principles of prevention, responsibility, justice, participation, sustainability, and restoration. The comparison of environmental law enforcement between Indonesia and Hungary in protecting indigenous communities reveals substantial similarities regarding the existence of legal instruments to regulate optimal environmental law enforcement. However, the regulations regarding the approach to legal pluralism related to environmental law enforcement in Indonesia and Hungary can be said to still be suboptimal. This research recommends that Indonesia needs a hybrid customary-state forum based on deliberation for the integration of state, customary, and religious laws based on pluralism, while Hungary requires reforms in line with the spirit of the EU Roma Framework 2030 thru post-disaster renovation to avoid environmental racism.